The Renaissance in Toronto: Early Modern Italian Books in the Collections of the Thomas Fisher Rare Book Library - Ricci, Antonio (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
The Thomas Fisher Rare Book Library at the University of Toronto has significant holdings of books printed in Italy during the Renaissance. These volumes cover a wide variety of disciplines and represent a major resource for scholars of literature, philosophy, science, and print culture. The article explains how the Renaissance material came to Toronto by tracing the historical formation of the rare books and special collections of the University Library. It then analyzes the main areas of strength of the Fisher’s early modern holdings, offering representative examples of the most important editions and of the outstanding bibliographic treasures. Finally, it briefly considers the contribution made by the Fisher Library to Renaissance studies in Canada in the last fifty years.